BATAGAK PENGHULU DI NAGARI PANINGGAHAN DALAM KARYA SENI LUKIS REALIS - Afandy, Drs. Efrizal, M.Pd., Drs. Irwan, M.Sn. (Universitas Negeri Padang, 2016)
This thesis aims to visualize of batagak penghulu in Nagari Paninggahan into realist painting. In determining the candidates to inherit the title of the families of the pusako in Nagari Paninggahan currently hard to get an agreement, because of the loss of a sense of mutual cooperation. It is interesting for the author to be appointed in a painting titled Batagak Penghulu in Nagari Paninggahan Realist Art in the Work. In the embodiment of ideas, the author subjects featuring human figures and other support that describes the activities Batagak penghulu. The author uses five stages in the creation of works of art, the preparation stage, the stage of elaboration, synthesis stage, the stage of realization of the concept, and the completion stage in the form of an exhibition of works end. Ten present writer created works with titles, namely: 1) “Musyawarah Kaum”, 2) “Pangulu”, 3) “Mambantai Kabau”, 4) “Maantan Jamba”, 5) “Hidangan Bajamba”, 6) “Pidotoa Pasambahan”, 7) “Pitunggua Laki-Laki”, 8) “Pitunggua Padusi”, 9) “Sumpah Janji Jabatan”, 10) “Baarak”. Each work displayed an activity of batagak penghulu in Nagari Paninggahan.Kata kunci: Batagak penghulu, seni lukis, realis